Do Complication Rates of Ventricular Drain Placement Differ between Twist Drill and Burr Hole in Acute Hydrocephalus? - Brand, Christine; Pala, Andrej; Kielhorn, Wilhelm; Wirtz, Christian Rainer; Kapapa, Thomas (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Objective The aim of the study was to compare two techniques for external ventricular drainage (EVD) placement with respect to their complication rates.Methods A retrospective descriptive study was performed to analyze all patients who had undergone EVD implantation for acute hydrocephalus between January 2010 and December 2013 with a focus on surgical technique and rate of complications. The burr hole technique (BHT) was used in one group and the twist-drill technique (TDT) in the other. Particular attention was paid to malposition, hemorrhage, and catheter-associated infection.Results A total of 350 consecutive patients underwent EVD implantation for acute hydrocephalus: BHT was performed in 201 and TDT in 147 of the patients, whereas in two patients the technique used was unknown. The overall infection rate was 6.3% (n = 22). Fourteen patients (4%) in the BHT group developed an infection compared with eight patients (9.5%) in the TDT group (p = 0.154). In 16 (4.5%) of all cases, postoperative computed tomography revealed catheter-induced hemorrhage.In one case (0.3%), surgery was necessary due to acute subdural hematoma. The difference between both techniques was not statistically significant (p = 0.343). In 44 (12.6%) of all cases, the position of the EVD tip was contralateral; in 36 (10.3%) of all cases, the EVD tip was in the brain parenchyma. The rate of malposition was 11.6% (n = 17) in the TDT group and 9.5% (n = 19) in the BHT group (p = 0.078).Conclusion Neither technique showed significantly different numbers in terms of infection, malposition, and hemorrhagic complications. EVD implantation using the TDT is an adequate method compared with BHT. The advantages of TDT are clear: the duration of surgery is shorter, the size of the wound is smaller, and the surgeon is not confined to the operating room.
Keywords: twist drill; burr hole; external ventricular drain infection; hydrocephalus; ventricular drain placement